Comparison of the behavioral effects of mescaline analogs using the head twitch response in mice. (March 2019) - Halberstadt, Adam L; Chatha, Muhammad; Chapman, Stephen J; Brandt, Simon D
Background: In recent years, there has been increasing scientific interest in the effects and pharmacology of serotonergic hallucinogens. While a large amount of experimental work has been conducted to characterize the behavioral response to hallucinogens in rodents, there has been little systematic investigation of mescaline and its analogs. The hallucinogenic potency of mescaline is increased by α-methylation and by homologation of the 4-methoxy group but it not clear whether these structural modifications have similar effects on the activity of mescaline in rodent models.Methods: In the present study, the head twitch response (HTR), a 5-HT2A receptor-mediated behavior induced by serotonergic hallucinogens, was used to assess the effects of mescaline and several analogs in C57BL/6J mice. HTR experiments were conducted with mescaline, escaline (4-ethoxy-3, 5-dimethoxyphenylethylamine) and proscaline (3, 5-dimethoxy-4-propoxyphenylethylamine), their α-methyl homologs TMA (3, 4, 5-trimethoxyamphetamine), 3C-E (4-ethoxy-3, 5-dimethoxyamphetamine) and 3C-P (3, 5-dimethoxy-4-propoxyamphetamine), and the 2, 4, 5-substituted regioisomers TMA-2 (2, 4, 5-trimethoxyamphetamine), MEM (4-ethoxy-2, 5-dimethoxyamphetamine) and MPM (2, 5-dimethoxy-4-propoxyamphetamine).Results: TMA induced the HTR and was twice as potent as mescaline. For both mescaline and TMA, replacing the 4-methoxy substituent with an ethoxy or propoxy group increased potency in the HTR assay. By contrast, although TMA-2 also induced the HTR with twice the potency of mescaline, potency was not altered by homologation of the 4-alkoxy group in TMA-2.Conclusions: The potency relationships for these compounds in mice closely parallel the human hallucinogenic data. These findings are consistent with evidence that 2, 4, 5- and 3, 4, 5-substituted phenylalkylamine hallucinogens exhibit distinct structure-activity relationships. These results provide additional evidence that the HTR assay can be used to investigate the structure-activity relationships of serotonergic hallucinogens.